PENERAPAN MESIN PENIRIS MINYAK (SPINNER) UNTUK MENINGKATKAN EFISIENSI PRODUKSI DAN KUALITAS DARI KERUPUK KULIT PADA IKM RIZKY DI KOTA PADANG - Indri Juliyarsi; Sri Melia; Ade Sukma; Rizki Dwi Setiawan; Ahmad Syafruddin Indrapriyatna; Tuty Anggraini (Jurnal Hilirisasi IPTEKS, 2022)
The process of making skin crackers, which is carried out in four stages of frying, results in a high oil content in the product. This is a separate obstacle for business actors in making skin crackers. A high oil content can cause rancidity in the product and requires a long time for oil draining in the production process. IKM partner "Rizky" which produces skin crackers in Lubuk Buaya, Padang City still uses a manual spinning process at each stage of frying. The purpose of this activity is to apply an oil spinning machine (spinner) in the process of making skin crackers at Mitra IKM "Rizky" to increase the production efficiency and quality of skin crackers. The method in this activity is carried out by providing a semi-automatic oil spinning machine followed by training and assistance in using an oil spinning machine and practicing from the first stage of frying to the last stage in making skin crackers. The result of this activity is that the use of an oil spinning machine can shorten the oil draining process time from 3.5 hours to 15 min without damaging the product. In addition, the use of an oil spinning machine provided more optimal oil extraction results than the manual spinning method. The oil content in the skin crackers decreased, thereby reducing the potential for rancidity in the product. The conclusion from this activity is that the use of oil-spinning machines in the skin cracker production process at Mitra IKM can increase the production efficiency and improve the quality of skin crackers.